English Language Learning Through Interactive Learning at SMA Al Amien Pamekasan - Anisatul Mafruhah; Saidatul Karimah (Institut Agama Islam Al-Fatimah Bojonegoro, 2025)
In the modern era, teachers must employ effective teaching methods, one of which is the interactive learning method. During the learning process, teachers need to actively engage students to create an interactive and educational environment that supports the achievement of learning objectives. The community service activity conducted at SMA Al Amien Pamekasan aimed to provide training for students on interactive learning to improve their English language skills. This activity was attended by 20 female students and consisted of four sessions: 1) Presentation on the importance of motivation in learning English; 2) Tips and tricks for learning English effectively; 3) Interactive learning through the application of role-play in English learning; and 4) Q&A/feedback session. The results of this activity demonstrated that students were highly enthusiastic about participating in the training and were motivated to learn English, leading to an improvement in their English proficiency compared to before. This was evident from interviews regarding students' perceptions and the positive responses they displayed throughout the learning process